The Evaluation of the Management Control System Implementation at PT Sukses Berkah Melimpah: Evaluasi Penerapan Sistem Pengendalian Manajemen pada PT Sukses Berkah Melimpah - Mulawarman, Logi; Jati, L. Jatmiko; Ramdani, Rizal; Widiyasti, Baiq Dinna; Putri, Dindi Sabila Iriani (Universitas Bumigora, 2023)
Every company should be able to survive in the midst of increasingly fierce competition by implementing a good management control system. However, now several companies still have problems in implementing management control systems. Thus, an evaluation is needed in the implementation of this system. The purpose of this research is to find out how the management control system is implemented at PT Sukses Berkah Melimpah. The method used is descriptive qualitative method. The results showed that the factors that influence the management control system such as culture, management style, information organization, perception and communication have been well implemented. The management of PT Sukses Berkah Melimpah should pay attention to internal factors that greatly affect the management control system, and it is even hoped that the control system will be further improved so that the company's goals can be achieved.